2018
DOI: 10.1007/s11162-018-9514-2
|View full text |Cite
|
Sign up to set email alerts
|

Bigger Pie, Bigger Slice? The Impact of Higher Education Expansion on Educational Opportunity in China

Abstract: China's higher education system has expanded rapidly since 1999. Exploiting variation in the density of university expansion across provinces and high school cohorts and applying a difference-in-differences model, we estimate the impact of higher education expansion on educational access and attainment with a particular focus on students' family and demographic backgrounds. Results indicate that the expansion of university spots increased both access and graduation rates at 4-year universities, but this improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Previous research has already shown the sharp increase in the total college enrollment from 1999 using aggregate data from the China National Bureau of Statistics (Yeung, 2013 ; Li et al., 2014 ; Ou & Hou, 2019 ). We present the first evidence on the differential changes in enrollment, inputs, and student access outcomes by institutional stratification.…”
Section: Data and Descriptive Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has already shown the sharp increase in the total college enrollment from 1999 using aggregate data from the China National Bureau of Statistics (Yeung, 2013 ; Li et al., 2014 ; Ou & Hou, 2019 ). We present the first evidence on the differential changes in enrollment, inputs, and student access outcomes by institutional stratification.…”
Section: Data and Descriptive Evidencementioning
confidence: 99%
“…First, we find evidence of the enlarging unequal access to elite higher education for students from different family backgrounds during the enrollment expansion, which supports the effectively or expanding maintained inequality theory (Lucas, 2001 ; Alon, 2009 ). These results speak to a large body of literature on higher education enrollment expansion and access in many countries, for instance, the United States (Taubman et al., 1972 ; Walters, 1984 ; Juhn et al., 2005 ; Barr & Turner, 2013 ; Soliz, 2018 ), France (Deer, 2005 ), the United Kingdom (Walker & Zhu, 2008 ; Boliver, 2011 ; Devereux & Fan, 2011 ), Italy (Bratti et al., 2008 ; Oppedisano, 2011 )), Germany (Reimer & Pollak, 2010 ), Turkey (Özoǧlu et al., 2016 ), Brazil (McCowan, 2007 ; Boliver, 2011 ; Dias et al., 2011 ), Ireland (McCoy & Smyth, 2011 ), and China (Luo et al., 2018 ; Ou & Hou, 2019 ). In particular, this paper shows new evidence of the expanding socioeconomic gaps in college access in the presence of higher education selectivity stratification.…”
Section: Introductionmentioning
confidence: 99%
“…We follow the decision rule that if the current province is the same as the hukou registered province and that individual did not leave the hukou registration province over the last five years, we assign the hukou registration province as the province where the individual graduated from high school. As we discuss in a later section, such a rule is reasonable given that the increases in university spots apply mainly to students registered in the same province where the universities are located (Hou and Ou, 2015). However, we discuss this further in the robustness check section.…”
Section: Methodsmentioning
confidence: 97%
“…In addition to the goal of investing in education for future development, the expansion of student spots in Chinese universities was also intended to increase domestic consumption and to relieve employment pressure on the labor market by absorbing high school graduates into college at a time when the nation was confronting the recession that resulted from the Asian financial crisis (Wan, 2006;Wu and Zhao, 2010;Wu & Zhang, 2010). , 1970-2012(Hou and Ou, 2015 Under the traditional central planning regime, higher education in China was heavily subsidized and mostly free. However, in 1997, just 2 years before the expansion policy was implemented, China enacted a universal tuition policy that gradually shifted responsibility for financing higher education from the government to families (Carnoy, 2011;Wang, Fleisher, Li and Li, 2007;Yeung, 2013).…”
Section: A Brief Overview Of Higher Education Expansion In Chinamentioning
confidence: 99%
See 1 more Smart Citation